Women, leadership and mosques : changes in contemporary Islamic authority - Bano, Masooda; Kalmbach, Hilary (Women and gender, the Middle East and the Islamic world, 2012)
The acceptance of female leadership in mosques and madrassas is a significant change from much historical practice, signalling the mainstream acceptance of some form of female Islamic authority in many places. This volume investigates the diverse range of female religious leadership present in contemporary Muslim communities in South, East and Central Asia, the Middle East, Africa, Europe, and North America, with chapters discussing its emergence, the limitations placed upon it, and its wider impact, as well as the physical and virtual spaces used by women to establish and consolidate their authority. It will be invaluable as a reference text, as it is the first to bring together analysis of female Islamic leadership in geographically and ideologically-diverse Muslim communities worldwide.